Arterial Stiffness Response to Regular Aerobic Training in Hypercholesterolemia Patients - Liu, Guanghui; Zhao, Jiasheng; Cao, Yang (International Journal of Sports Medicine, 2018)
Physical exercise increase is confirmed as a fundamental treatment for hypercholesterolemia patients, but the effect on the arterial stiffness and oxidative stress is still unclear. 74 hypercholesterolemia patients were divided into 2 groups. The exercise group received dietary recommendations and a 3-month exercise program, prescribed according to their first cardiopulmonary exercise tests(CPET), while the control group only received dietary recommendations. All patients underwent blood tests, CPET and brachial-ankle pulse wave velocity (baPWV) studies at enrollment and at 3 months’ follow-up. At the end of 3 months, there was no change in total cholesterol (TC) level in either group. However, in the exercise group, we found maximal exercise parameters increased and baPWV values declined. Meanwhile, there were significant changes in the level of malondialdehyde, 8-isoprostane-F2α and superoxide dismutase. Moreover, the change of baPWV was positively correlated with the change of 8-isoprostane-F2α (r=0.36, P<0.01). In the control group, no change in baPWV or oxidative biomarker was observed. Our findings suggested that regular aerobic exercise could lessen arterial stiffness in hypercholesterolemia patients, even in the context of no obvious TC decrease. During this process, favorable adjustment in oxidative stress might be an important pathway, which remains to be further explored.
Keywords: arterial stiffness; aerobic training; hypercholesterolemia; oxidative stress